Avaliação da percepção ambiental dos moradores do bairro Condá da cidade de Medianeira por intermédio de alunos do ensino fundamental I - Schmitz, Roseli Maria (2013)
This work had as thematic the environment perception, having as general objective to evaluate as the environment is perceived by the residents of Condá neighborhood in the city of Medianeira, through Idalina Pasquotto Bonatto municipal school students with the focus in solid residues and the 3R's politics for, from the survey of the perceptions and practice of the pupils about environment and environmental problems, as well as its Inter-relations with the involved social actors in the process, to subsidize the development of interdisciplinary environmental education projects and participatives to the school resume. One applied questionnaires to the pupils, teachers and collaborators, the perceptions on environmental subjects as environment, water and garbage had been analyzed resulting in answers categories. They noticed in relation to the boarded subjects, that the pupils consider themselves the main responsables for taking care of the environment, being this of basic importance for our survival, being also animals and plants part of it. In relation to the water, this was related to the life, and exactly thus, the majority of the interviewed ones classified it as being an exhaustible resource for wastefulness, pollution and lack of people awareness. The garbage was related to everything that cannot be reused or recycled anymore, things that we do not use anymore and we throw out. The perception of the involved ones is really favorable and can guide in the development of works directed to the community improvement in general and also in the development of environmental education projects in the school. It is also possible to guide the introduction of a project of selective collection in the institution, and also the use of practices of the 3R’s politics, to reduce, to recycle and to reuse, since the pupils had demonstrated to have knowledge on the subject.